Study of the population in terms of knowledge about the distance between vehicles in motion - Olejnik Krzysztof (De Gruyter, 2021)
When using vehicles on the road, road users are exposed to accidents. The human factor contributes greatly to their occurrence. The article presents pilot studies on the state of knowledge of drivers referring to maintaining the necessary distance behind the preceding vehicle in road traffic. The state of knowledge governing applicable law in the field of distance between vehicles was also examined. They were carried out by a group of employees using road transport and students. Even with the new technical devices which determine distance, in addition to the lack of knowledge of drivers in the discussed area, dangers of hitting a preceding vehicle in extreme situations still exist. These are activities in the area of the active safety system in the operation of vehicles in road traffic. The conclusions indicate the need to conduct management training and to amend the provisions in the applicable road traffic law.